IMPROVING METHODS OF ASSESSING AND MANAGING AUDIT RISKS IN JOINT-STOCK COMPANIES - Khalimova Mayram Khamidovna (Ecomind Press, 2025)
Improving methods of assessing and managing audit risks in joint-stock companies is an important aspect of corporate governance. This article examines modern approaches aimed at identifying, assessing and minimizing financial risks in the audit process. Methods of risk analysis, strengthening internal control systems and ensuring information confidentiality based on International Standards on Auditing (ISA) are analyzed. The article offers innovative strategies and practical recommendations for improving the efficiency of audit activities in joint-stock companies.
Keywords: Joint-stock companies, audit, risk assessment, risk management, financial risk, internal control, international standards, information confidentiality, corporate governance, audit effectiveness, innovative strategies, practical recommendations.